The Effect of Submaximal Exercise on Blood Creatinine, Urea, Total Protein and Uric Acid Levels of Trained and Untrained Subjects - Alina Gailiūnienė; Arvydas Stasiulis; Jolanta Michailovienė (Lithuanian Sports University, 2018)
There are numerous studies about exercise-induced sports hematuria, proteinuria, acute renal failure following a marathon (Steward, Posen, 1980; Poortmans et al., 2001; Ayca et al., 2006). But studies investigating the effects of exercise on blood indicators of renal function are quite few. The aim of this study was to investigate the effects of submaximal veloergometric exercise on very important bio- chemical indicators of renal function - level nitrogen compounds in the blood. We investigated concentration of creatinine, urea, total protein and uric acid in venous blood samples before and after submaximal veloergometric exercise. Those nitrogen compounds were studied in three groups of subjects. The study was performed with 10 trained (Group 1), 10 untrained subjects (Group 2) and 10 subjects with I o  hiper- tensive status (Group 3). The age range was 20.5-21.3 years, weight - 71.8-77.3 kg, height - 180-177 cm. All subjects voluntered to participate in the study after providing written informed consent. The study was approved in accordance with the Declaration of Helsinki. Blood samples were collected before and after the submaximal velo- ergometric test into vacumtrainer tubes. Concentrations of creatinine, urea, total protein and uric acid in the serum were determined using Technicon Auto Analyzer ADVIA 1650 system. All data were reported as mean ± standard deviation (SD) unless otherwise speciﬁ ed, and statistical signiﬁ cance was recognized when p ≤ 0.05. No statistically signiﬁ cant difference was observed between pre- and post exercise blood creatinine, urea, total protein and uric acid mean levels of all group subjects. A marked exercise induced increase in blood creatinine and total protein concentrations was observed when the results of trained and untrained participants' parameter differences were compared after the exercise. A signiﬁ cant (p < 0.05) exercise-induced increase in blood urea and total protein concentration was observed when the mean values of Group 1 and Group 2 before the exercise and parameters after the exercise were compared. When blood creatinine, urea, total protein and uric acid levels were compared separately for the participants, it was observed that seven persons in Group 1 and three persons in Group 2 showed a marked exercise-induced increase in the blood nitrogen compounds level. Research results suggest that 1) the testing exercise-induced statistically insigniﬁ cant (p > 0.05) increases in the blood parameters of nitrogen compounds (creatinine, urea, total protein and uric acid) could be due to the common phenomenon of the physical stress and catecholamine effects, 2) postexercise changes of blood nitrogen compounds were signiﬁ cant (p < 0.05) when the results of Group 1 with Group 2 participants were compared. The signiﬁ cant differences in metabolic responce in Group 1 and  Group 2 participants probably reﬂ ect differences in work volume and intensity, and 3) further studies are needed to be performed on more subjects to evaluate exercise-speciﬁ c effects on postexercise changes of blood nitrogen compounds in athletes and nonathletes. Keywords: blood, creatinine, urea, total protein, uric acid.